Trajetória de um discente cego na universidade: limites e possibilidades - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Brazil is a country where social problems have been taking on new dimensions through programs and incentives for public policies and inclusion, in the repair of human rights violations. The theoretical references that were used in this work were inclusion as a political agenda that seeks knowledge and understanding about the policies that govern education, the declaration of human rights, which is a document that recognizes the dignity and right of human beings as freedom of expression without any kind of censorship, Jontien's declaration that it is a plan of action to satisfy basic learning needs, Salamanca's declaration through another recall of the various declarations of the united nations, the LDB - Law of Guidelines and Bases of Education, LBI Brazilian Law of Inclusion of Persons with Disabilities (Statute of Persons with Disabilities) which addresses the barriers listed by legislation that show the factors that end up making it impossible for people with disabilities to be included in society, Law No. 11126 which serves to ensure the right of the visually impaired individual to enter and remain in environments for collective use. the use of a guide dog, Law no 4169 being specific for people with visual impairment, ensuring the right to use Braille, the national policy of special education in the perspective of inclusive education, Law no 12711 which provided for the rights of people with disabilities entering federal universities and secondary technical level institutions and new inclusive legislation in basic education that instituted the national policy of equitable, inclusive and lifelong learning special education. The work methodology was a qualitative approach anchored in the critical incident technique, seeking to report the experiences and difficulties of a blind student during their trajectory in the interdisciplinary bachelor's degree in science and technology (BICT) course at Unipampa campus Itaqui. In the results and discussions, the situations and experiences during his trajectory at the university, which began after the completion of high school, were reported. Therefore, this work presents the challenges faced by those a blind student, where it was possible to report the advances, the difficulties and also the movements made by society in the search for quality and inclusive education for all.
Keywords: Deficiência visual; Acessibilidade; Politicas públicas; Inclusão; LDB; LBI; Lei de Diretrizes e Bases da Educação; Lei Brasileira de Inclusão da pessoa com deficiência; Visual impairment; Accessibility; Public policy; Inclusion; Law on Education Guidelines and Bases; Brazilian Law for the Inclusion of Persons with Disabilities; CNPQ::CIENCIAS EXATAS E DA TERRA